Odpowiedź :
Odpowiedź:
2x-1=4x+5
2x-4x=5+1
-2x=6/:(-2)
x=-3
(2x-1+(3x-1)=2x+2
2x+3x-2x=2+1+1
3x=4/:3
x=⁴/₃
x=1¹/₃
(1x-2)-(2+2)=4-2x
x-2-2-2=4-2x
x+2x=4+6
3x=10/:3
x=¹⁰/₃
x=3¹/₃
(4-2x)-(2x+2)=x
4-2x-2x-2=x
-4x-x=-2
-5x=-2/:(-5)
x=²/₅
Szczegółowe wyjaśnienie:
1)
2x-1=4x+5 /-4x
2x-1-4x=5 /+1
-2x=6. /:(-2)
x=(-3)
2)
2x-1+3x-1=2x+2. /-2x
-2+3x=2. /-2
3x=0
jest to rownanie sprzeczne
3)
x-2-2-2=4-2x. /-2x
x-6-2x=4
-3x-6=4. /+6
-3x=10. /:(-3)
x= (-3 1/3)
4)
4-2x-2x-2=x
2-4x=x /-2
-4x=x-2. /-x
-5x=(-2). /:(-5)
x= 2/5
2x-1=4x+5 /-4x
2x-1-4x=5 /+1
-2x=6. /:(-2)
x=(-3)
2)
2x-1+3x-1=2x+2. /-2x
-2+3x=2. /-2
3x=0
jest to rownanie sprzeczne
3)
x-2-2-2=4-2x. /-2x
x-6-2x=4
-3x-6=4. /+6
-3x=10. /:(-3)
x= (-3 1/3)
4)
4-2x-2x-2=x
2-4x=x /-2
-4x=x-2. /-x
-5x=(-2). /:(-5)
x= 2/5